ChemInform Abstract: One‐Pot Tandem Synthesis of Tetrasubstituted Pyrazoles via 1, 3‐Dipolar Cycloaddition Between Aryl Hydrazones and Ethyl But‐2‐ynoate. Issue 49 (9th December 2014) - Ningaiah, Srikantamurthy; Doddaramappa, Shridevi D.; Chandra, Chandra; Madegowda, Mahendra; Keshavamurthy, Shubakara; Bhadraiah, Umesha K.
Abstract The title reaction is assumed to occur via the regioselective cycloaddition reaction of aryl hydrazones with nitrilimines generated in situ.